Pengaruh Penambahan Karet Alam Cair (Lateks) terhadap Kuat Tekan Marshall pada Campuran Aspal AC-WC - Finanditho, Billy; Das, Amsori M.; Zulfiati, Ria (Jurnal Talenta Sipil, 2025)
To improve each quality of 60/70 penetration oil asphalt so that it becomes harder, has a high softening point, is more elastic, has good adhesion and is more durable, it is necessary to add other materials and in this research it was tried with Laston AC-WC using additional materials. liquid natural rubber (latex) This research is expected to determine the characteristics of adding liquid natural rubber to the Optimum Asphalt Content (KAO) based on Marshall parameters, so that it can provide good results for flexible pavements in the future. The aim of this research is to obtain optimum asphalt content values with asphalt percentage variations of 4.5%, 5%, 5.5%, 6%, 6.5%, and 7% from the Marshall Compressive Strength Test results and to obtain content values optimum asphalt with variations in the percentage of liquid natural rubber of 3%, 5%, 7% and 9% from the Marshall Compressive Strength Test results. The research method used was an experiment in the laboratory based on the 2018 Revision 2 Technical Specifications. From this research, the results were that KAO from test results with variations in standard asphalt was 5.9% and KAO from marshall test results with variations in liquid natural rubber content was 4.5%.